2011
DOI: 10.1007/s11325-011-0557-2
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of obstructive sleep apnoea and metabolic syndrome is independently associated with left ventricular hypertrophy and diastolic dysfunction

Abstract: Coexistent severe OSA and MS can exacerbate LV concentric hypertrophy. However, not only the coexistence of these two disorders, but also either severe OSA or MS can impair LV diastolic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…These results are consistent with a previous large cross-sectional study by Niroumand et al, who found no significant difference in the E/A ratio between OSAS and non-OSAS patients [15]. However, in several other studies, associations were reported between OSAS severity and E/A ratio [35,36], A peak wave [36] or LA volume [37], with reversibility after a few months of CPAP treatment [33,37,38]. Furthermore, AHI was significantly correlated Left ventricular diastolic function in obstructive sleep apnoea syndrome 9 with LAA, which is a surrogate for diastolic function.…”
Section: Left Ventricular Diastolic Functionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with a previous large cross-sectional study by Niroumand et al, who found no significant difference in the E/A ratio between OSAS and non-OSAS patients [15]. However, in several other studies, associations were reported between OSAS severity and E/A ratio [35,36], A peak wave [36] or LA volume [37], with reversibility after a few months of CPAP treatment [33,37,38]. Furthermore, AHI was significantly correlated Left ventricular diastolic function in obstructive sleep apnoea syndrome 9 with LAA, which is a surrogate for diastolic function.…”
Section: Left Ventricular Diastolic Functionsupporting
confidence: 93%
“…Indeed, Noda et al defined LVH according to interventricular septum or posterior wall thickness, without LVM calculation [32]. Likewise, several studies assessed LVH by LVMi normalized by BSA only [12][13][14]35]. Finally, LVH defined using LVMi normalized by height was more often eccentric than concentric, as found by Chami et al [31], with a significant correlation between LV diameters and desaturation time but not AHI.…”
Section: Left Ventricular Geometrymentioning
confidence: 99%
“…This finding confirms the significant impact of OSA on systolic function. It was supported by the results of Usui et al that patients with OSA have worsened systolic function as assessed by the STE method [22].…”
Section: Prace Oryginalnementioning
confidence: 73%
“…Most recent studies show a persistent independent relationship between OSAS and LVMi (height) after adjustment for confounding factors or multivariable analysis [33,35,38,39,47,52]. However, few studies have reported no significant association between LVMi (BSA) [49,53] or LVMi (height) [41,48] and OSAS after taking into account confounding factors. Despite these discrepancies, we can reasonably think that OSAS is independently associated with LVMi, and that in addition to this, OSAS, BMI and AHT have significant interacting effects on LVMi [47].…”
Section: Effect Of Measurement Methods On LV Geometrymentioning
confidence: 99%
“…Indeed, some studies reported a significant correlation between LVMi and OSAS severity variables after multivariable analysis including BMI [39,47], whereas others did not [41]. Furthermore, several studies reported that, after multivariable analysis, LVMi was determined by metabolic syndrome, but not by BMI [48,49].…”
Section: Remodelling In Osas Beyond Obesitymentioning
confidence: 99%